Effect of different sowing densities and substrates on the growth of arugula seedlings - Menegaes, Janine Farias; Fiorin, Tatiana Tasquetto (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2023)
Arugula is known for the spicy flavour of its leaves, and it is an important crop due to its high productivity and multiple harvests per year. However, seedling quality may limit its production. This study examined arugula seedling emergence and production at different sowing densities and substrate compositions. In a greenhouse, the broadleaf cultivar was randomized with a 5×3 factorial design (substrate compositions: 100% medium textured sand (SD), 100% Carolina Soil® commercial substrates (CS), 50%SD+50%CS, 75%SD+25%CS, and 25%SD+75%CS, and sowing densities: 5; 10 and 15 seeds/alveolus); with five replications. Analyzes were carried out on emergence speed index and mean emergence time, as well as on relative frequency, lengths of aerial and root parts, number of leaves, and rating scales according quality for tuft formation (or bouquets) and clod stability. All seeding densities and substrate compositions showed good seedling formation, except for the 100% SD composition, which showed low adherence in the substrate-plant-container-water system for tuft formation and clod stability. Except for 100% SD composition, an average of 70% of seedling emergence was at 9.7 d. For the production of commercial seedlings, it is indicated the use of 10 or more seeds per alveolus, and all substrate compositions tested in this study, except 100% SD.